2020
DOI: 10.1016/j.ijforecast.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Can Google search data help predict macroeconomic series?

Abstract: We use Google search data with the aim of predicting unemployment, CPI and consumer confidence for the US, UK, Canada, Germany and Japan. Google search queries have previously proven valuable in predicting macroeconomic variables in an in-sample context. To our knowledge, the more challenging question of whether such data have out-of-sample predictive value has not yet been satisfactorily answered. We focus on out-of-sample nowcasting, and extend the Bayesian Structural Time Series model using the Hamiltonian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the last decade, this idea has produced a fruitful literature with, in particular, many papers focused on predicting the evolution of the labor market. Some examples are the studies by Varian (2009, 2012); Pavlicek and Kristoufek (2015); Niesert et al (2020) and Caperna et al (2020). Other papers, closer to ours, will be discussed in the next section.…”
Section: Introductionmentioning
confidence: 73%
“…In the last decade, this idea has produced a fruitful literature with, in particular, many papers focused on predicting the evolution of the labor market. Some examples are the studies by Varian (2009, 2012); Pavlicek and Kristoufek (2015); Niesert et al (2020) and Caperna et al (2020). Other papers, closer to ours, will be discussed in the next section.…”
Section: Introductionmentioning
confidence: 73%
“…More recently, Niesert et al (2019) obtained data from Google to forecast macroeconomic series, and they concluded that predictive power of the Internet queries is higher for those series that are directly linked to personal situations, such as employment status. There some other recent economic applications, such as Yu et al (2019), who demonstrated that forecasting models that include data from Google Trends outperform traditional ones when predicting oil consumption trend and level.…”
Section: Introductionmentioning
confidence: 99%
“…Further, survey data can be also available at a regional level. Recently, Google search data have been shown to have predictive power for unemployment (e.g., Caperna et al, 2022;Choi & Varian, 2009;D'Amuri & Marcucci, 2017;Fondeur & Karamé, 2013;Nagao et al, 2019;Niesert et al, 2020). Their main advantages are that they are free from revisions and can be obtained in specific geographical areas, such as the region of a country.…”
Section: Introductionmentioning
confidence: 99%